Cutaneous melanoma in adolescents and young adults. Issue 11 (3rd July 2018) - Indini, Alice; Brecht, Ines; Del Vecchio, Michele; Sultan, Iyad; Signoroni, Stefano; Ferrari, Andrea
Abstract: Cutaneous melanoma is rare in children, but has greater incidence in adolescents and young adults (AYAs). Diagnosis may be challenging due to its rarity in these age groups. Few studies have specifically addressed the topic of AYA melanoma. Though young‐age melanoma may have particular biological characteristics, available data suggest that its clinical history is similar to that of adults. However, advances in treatment of adult melanoma have not been reflected in the treatment of AYAs. There is no standard treatment, and access to clinical trials is difficult for AYAs. Further efforts are needed to overcome these issues by improving cooperation with experts on adult melanoma.